Closer look at vortical hot towers within a tropical cyclogenesis environment - Saunders, Andrea B., author; Montgomery, Michael T., author (Colorado State University. Libraries, 2004)
It is a generally accepted fact that convection plays an important role in tropical cyclone intensification, yet convective-scale processes are absent from many tropical cyclogenesis theories. Results from cloud-resolving, full-physics simulations carried out with the CSU RAMS suggest that convective-scale dynamical processes play a significant, if not crucial, role in the transition from a midlevel MCV to a tropical cyclone. In addition, deep convective hot towers occurring within this environment possess large, localized positive vertical vorticity values generated by the tilting and stretching of MCV related vorticity on the updraft scale. This study seeks to understand both the role that deep convection plays in tropical cyclone formation and how the vortical nature of these hot towers influences the formation process. First, we conduct a simple correlation analysis to demonstrate that deep convective activity is statistically related to mesoscale intensification. This analysis confirms that intensification of the midlevel mesoscale vortex lags deep convective bursts by a few hours. Next, we review a theory that explains how convective-scale processes induce spin up of the mesoscale circulation using Eliassen's balanced vortex model. The mesoscale meridional and tangential circulations predicted by this theory are qualitatively and quantitatively similar to those predicted by the model, with the dominant forcing for the balance equations being contributions from quasi-steady, deep convective activity in the form of the diabatic heating term. We next address the question as to why the MCV environment is conducive to such quasi-steady convective activity. To answer this question, we must determine how the mesoscale environment influences hot tower characteristics. The most notable influence is the contribution of ambient vorticity which leads to the formation of vortical hot towers (VHT). Preliminary results from a series of sensitivity trials for an isolated updraft suggest that vorticity has a positive influence on individual updraft lifetimes and future updraft formation. The simulations also demonstrate that the moderate vertical shear present in the parent MCV leads to a tilting of VHTs downshear with height. This orientation displaces the cool dry downdraft air from the updraft core which delays the decay of the updraft. It appears that both the ambient vorticity and moderate vertical shear of an MCV play roles in the sustenance of deep convective activity in these simulations. However, the exact nature of these relationships is still unclear. Further high-resolution simulations and analyses, as well as convective-scale observations of tropical cyclogenesis environments, are advocated to test the robustness of the vortical hot tower phenomenology.
May 2004.
Also issued as Andrea B. Saunders's thesis (M.S.) -- Colorado State University, 2004.
Keywords: Cyclones -- Tropic; Vortex-motion; Convection (Meteorology)